Cultivating Pro-environmental Literacy in Future Primary School Teachers: A Pathway to Sustainable Education - Dita Destiana; Resyi Abdul Gani; Fitri Siti Sundari; Aanisah Nur Fitriany (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
The aims of this study is to reveal the picture of pro-environmental education in elementary school teacher education students. The research sample through convenience sampling is 100 elementary school teacher training students of Pakuan University. Qualitative research methods, descriptive approaches with survey data collection techniques using questionnaire instruments and multiple-choice question tests were used to determine the percentage of students' pro-environmental literacy consisting of indicators of environmental knowledge, cognitive skills, environmental attitudes and pro-environmental behavior. The results of data processing and analysis showed that the environmental education of primary school teacher education students (PGSD students) was at a moderate level, the indicators of environmental knowledge (78.3%), cognitive skills (63.3%) and pro-environmental behavior were at a moderate level (65.6%), and attitudes towards knowledge were in the high category with a percentage (81%). In addition, the percentage also shows several sub-indicators with the highest percentage of environmental literacy, including the sub-indicator of problem-solving knowledge, the environment above the environmental literacy indicator, the sub-indicator has the ability to plan activities to investigate environmental problems on the cognitive skills indicator, the environmental assessment sub-indicator on the environmental care attitude indicator and the eco-friendly consumption sub-indicator on the pro-environmental behavior. The hope of most students is to expect more activities on campus that combine academic learning with environmental practices.